The application of epidemiology in aquatic animal health -opportunities and challenges - Peeler Edmund J; Taylor Nicholas GH (Veterinary Research, 2011)
Abstract Over recent years the growth in aquaculture, accompanied by the emergence of new and transboundary diseases, has stimulated epidemiological studies of aquatic animal diseases. Great potential exists for both observational and theoretical approaches to investigate the processes driving emergence but, to date, compared to terrestrial systems, relatively few studies exist in aquatic animals. Research using risk methods has assessed routes of introduction of aquatic animal pathogens to facilitate safe trade (e.g. import risk analyses) and support biosecurity. Epidemiological studies of risk factors for disease in aquaculture (most notably Atlantic salmon farming) have effectively supported control measures. Methods developed for terrestrial livestock diseases (e.g. risk-based surveillance) could improve the capacity of aquatic animal surveillance systems to detect disease incursions and emergence. The study of disease in wild populations presents many challenges and the judicious use of theoretical models offers some solutions. Models, parameterised from observational studies of host pathogen interactions, have been used to extrapolate estimates of impacts on the individual to the population level. These have proved effective in estimating the likely impact of parasite infections on wild salmonid populations in Switzerland and Canada (where the importance of farmed salmon as a reservoir of infection was investigated). A lack of data is often the key constraint in the application of new approaches to surveillance and modelling. The need for epidemiological approaches to protect aquatic animal health will inevitably increase in the face of the combined challenges of climate change, increasing anthropogenic pressures, limited water sources and the growth in aquaculture. Table of contents 1 Introduction 4 2 The development of aquatic epidemiology 7 3 Transboundary and emerging diseases 9 3.1 Import risk analysis (IRA) 10 3.2 Aquaculture and disease emergence 11 3.3 Climate change and disease emergence 13 3.4 Outbreak investigations 13 4 Surveillance and surveys 15 4.1 Investigation of disease prevalence 15 4.2 Developments in surveillance methodology 16 4.2.1 Risk-based surveillance and scenario tree modelling 16 4.2.2 Spatial and temporal analysis 16 4.3 Test validation 17 5 Spread, establishment and impact of pathogens 18 5.1 Identifying routes of spread 18 5.1.1 Ex-ante studies of disease spread 19 5.1.2 Ex-post observational studies 21 5.2 Identifying risk factors for disease establishment 23 5.3 Assessing impact at the population level 24 5.3.1 Recording mortality 24 5.3.2 Farm health and production records 26 5.3.3 Assessing the impact of disease in wild populations 27 6 Conclusions 31 7 Competing interests 32 8 Authors' contributions 32 9 Acknowledgements 33 10 References 33